Agrarian legislation of interwar Poland: specificities of its implementation in Eastern Galicia - Vitaliy Vyzdryk; Oleksandra Melnyk; Oleg Muravskiy (Cхід)
Reforming the legal framework of the agrarian legislation of the Second Polish Republic lied in the need to improve socio-economic changes in the system of agrarian land-use. An important basis for this process was supposed to be the creation of a proper legal framework, which, by ensuring the inviolability of private land ownership, created opportunities for the formation and strengthening of farms and would contribute to the elimination of landlessness and land hunger. The implementation of the laws of 1919 and 1920 in the agricultural sector was extremely slow, which forced to seek new ways and approaches to its reforming. In view of the difficult political situation in the eastern and southeastern provinces, taking into account the demands of political forces for reforming land relations in the interest of the peasants, the Sejm adopted a new law on the “Implementation of Agrarian Reform”, which came into force in December 1925. This legislative act determined the basic parameters of agrarian sector reforming up to 1939. Although Poland’s agrarian legislation largely protected the interests of large landowners, it at the same time contributed to the creation of new farms, improved the mechanism of legal registration of land rights, which strengthened civilized market relations in the economic sector. Separate legislative acts (1923, 1928, 1932 years) normalized the elimination of strip cropping and strip farming (comasation), which slowed the development of intensive agriculture; regulated leasing relations in the agricultural sector, which contributed to its transition to market conditions of functioning; allowed land reclamation works with the aim of optimizing the use of soil potential. State agrarian legislation and government policy had exacerbated national and social contradictions in society. Warsaw’s intention to change the quantitative relation of the Ukrainian and Polish populations in favor of the latter through the resettlement of colonists from the Polish ethnic territory to western Ukrainian lands, which were supposed to create strong households and become an important social and political support of the authorities, had failed.